2014
DOI: 10.1063/1.4894820
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a commercial shear rheometer for applications in cartilage research

Abstract: Cartilage research typically requires a broad range of experimental characterization techniques and thus various testing setups. Here, we describe how several of those tests can be performed with a single experimental platform, i.e. a commercial shear rheometer. Although primarily designed for shear experiments, such a rheometer can be equipped with different adapters to perform indentation and creep measurements, quantify alterations in the sample thickness, and conduct friction measurements in addition to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Furthermore, the gelation profile showed that the hydrogel system provided a suitable time window between the gelation point at about 2 min, after which embedded cells do not rapidly sink to the bottom any more, and an ongoing gelation and crosslinking for over 1 h, to result in well‐distributed cells incorporated within the hydrogels. The hydrogels were observed to be considerably softer in comparison to native cartilage, for which an elastic modulus of ≈0.4–0.6 MPa was reported . However, a hydrogel stiffness similar to that determined for the hydrogels developed in this study has previously been shown to be suitable in cartilage engineering for robust chondrogenic differentiation of MSCs …”
Section: Resultssupporting
confidence: 68%
“…Furthermore, the gelation profile showed that the hydrogel system provided a suitable time window between the gelation point at about 2 min, after which embedded cells do not rapidly sink to the bottom any more, and an ongoing gelation and crosslinking for over 1 h, to result in well‐distributed cells incorporated within the hydrogels. The hydrogels were observed to be considerably softer in comparison to native cartilage, for which an elastic modulus of ≈0.4–0.6 MPa was reported . However, a hydrogel stiffness similar to that determined for the hydrogels developed in this study has previously been shown to be suitable in cartilage engineering for robust chondrogenic differentiation of MSCs …”
Section: Resultssupporting
confidence: 68%
“…[ 53 ] and shown as an inset in Figure 2 B. As friction partners in the tribology setup, PDMS cylinders and steel spheres with a diameter of 12.7 mm (Kugel Pompel) were chosen.…”
Section: −3mentioning
confidence: 99%
“…We next repeated our comparison of different lubricants with a macroscopic method, i.e. a rotational macrotribometer (see Boettcher et al, 2014 for more details). Here, a glass sphere in contact with three cartilage samples was rotated with a constant velocity (Fig.…”
Section: Macro-friction Experimentsmentioning
confidence: 99%
“…The test procedure was described in detail by Boettcher et al (2014). In short, a glass sphere with a diameter of ½ in.…”
Section: Rotational Tribometermentioning
confidence: 99%
See 1 more Smart Citation